Tf2O-Promoted Morgan–Walls Reaction: From a Flexible Approach to Functionalized Phenanthridines and Quinazolines to the Short and Divergent Total Syntheses of Alkaloids - Su, Xiao-Yu; Huang, Pei-Qiang (Synthesis, 2022)
A new protocol for the direct transformation of secondary amides (N-acyl-o-xenylamines) to phenanthridines under mild conditions is reported. The method features trifluoromethanesulfonic anhydride (Tf2O)/2-fluoropyridine as the efficient amide activation system and MeCN or CH2Cl2 as the solvent. For some substrates, MeCN participated in the reaction, which affords a mild access to polysubstituted quinazolines. By employing a Tf2O/2,4,6-tri-tert-butylpyrimidine (TTBP) combination, the method was extended to an N-formyl-o-xenylamine, which represents a recalcitrant amide substrate type for the dehydrative cyclization reaction. More importantly, a one-pot method was established for the direct and divergent synthesis of four types of phenanthridinoids from o-xenylamines, which features both a tert-N-formyl-o-xenylamine and phenanthridinium salt as key and versatile intermediates. The investigation has resulted in one of the shortest and the most efficient total syntheses of the three natural products trisphaeridine, 5,6-dihydrobicolorine, and N-methylcrinasiadine, and in the formal total syntheses of three other ones: 3-hydroxytrisphaeridine, bicolorine, and zephycandidine A.
Keywords: amide activation; N-heterocycles; cyclization; step-economy; chemoselectivity; alkaloids; total synthesis; Morgan–Walls reaction